The Business Plan: Al-Amin Living Lab and Industrial Park of Goat Farming - Lubis, Hidayati Purnama; Siswoyo, Purwo; Rangkuty, Dewi Mahrani; Dewi, Tridia Kumala (The Eastasouth Management and Business, 2024)
The goal of this research is to examine and assess the business plan for goat farming within the Al-Amin Living Lab and Industrial Park area, located in Kutalimbaru District, Sampe Cita Village. The specific target of this research is to find the factors that influence the development strategy of the goat farming business plan in the Al-Amin Living Lab and Industrial Park area in Kutalimbaru District, Sampe Cita Village. So that in making decisions to determine strategies that can create success in the goat farming business. This research uses a Quantitative Descriptive research approach, where this study is related to data that describes the factors and success strategies in building a goat farming business in the Al-Amin Living Lab and Industrial Park area in Kutalimbaru District, Sampe Cita Village. The data analysis used is SWOT analysis, a strategic planning method used to Evaluate Strengths, Weaknesses, Opportunities, and Threats that occur in projects or a business venture. The results of the study explain that the results of the analysis of non-financial aspects, namely market aspects, technical aspects, management aspects, legal aspects, and social aspects, the sheep fattening business is feasible to implement. The results of the analysis of financial aspects which include NPV, IRR, Net B/C, and payback period, this sheep-fattening business is feasible to implement.